Fall fisheries investigation in the Athabasca and Clearwater rivers upstream of Fort McMurray Vol I ... - McCart, P. J.; Mann, G. J.; Jones, M. L. (University of Alberta Library, 1978)
Fisheries investigations were undertaken in the Athabasca and Clearwater rivers upstream of Fort McMurray in the fall of 1977. The major emphasis of these studies was to delineate actual and potential spawning areas for lake whitefish in the Athabasca and Clearwater rivers. Lake whitefish were found to spawn during mid-October in the mainstem of the Athabasca River from Fort McMurray upstream to Cascade Rapids, a distance of approximately 32 km. The major concentrations of spawning lake whitefish were immediately below Mountain Rapids (24 km upstream of Fort McMurray). There was no evidence of lake whitefish spawning in the Clearwater River. Spawning generally occurred in fast water over broken rock, rubble, and coarse gravel substrates. While recaptures were insufficient to calculate a population estimate by scientific means, the spawning population is large, certainly numbering tens of thousands of fish. Post-spawning tag returns indicate that the lake whitefish spawners moved downstream immediately after ...